The Local Nature of Hypothesis Tests Involving Inequality Constraints in Nonlinear Models - Wolak, Frank A. (Econometrica, 1991)
This paper derives several properties unique to nonlinear model hypothesis testing problems involving linear or nonlinear inequality constraints in the null or alternative hypothesis. The paper is organized around a lemma that characterizes the set containing the least favorable parameter value for a nonlinear model inequality constraints hypothesis test. The author then presents two examples that illustrate several implications of this lemma. He also discusses the impact of these properties on the empirical implementation and interpretation of these test procedures. Copyright 1991 by The Econometric Society.